A simple approach to prevent skin damage from heat steam in robotic breast surgery - Chen, Kuo; Lu, Pengwei (Frontiers in Oncology, 2025)
ObjectiveTo prevent heat-steam-induced skin damage during robotic nipple-sparing mastectomy with immediate breast reconstruction (RNSMIBR). Methods: Clinical data from 156 breast cancer patients undergoing RNSMIBR were analyzed retrospectively. Patients were divided into three groups: no skin cooling (group A, 29 cases), gauze cooled by ice water (group B, 99 cases), and gauze with ice water combined with suction tubing (group C, 28 cases). Key parameters such as age, BMI, and cancer pathology showed no significant differences across groups (P>0.05). Intraoperative skin temperature, mastectomy duration, and complications from heat-steam-induced skin damage were recorded.ResultsGroups B and C had significantly lower skin temperatures compared to group A (P<0.01). Heat-steam skin damage occurred in seven cases: five in group A and two in group B (P<0.05). One group A patient experienced severe complications, requiring implant removal.ConclusionCooling breast skin with ice-water-soaked gauze combined with suction tubing during RNSMIBR significantly reduces the risk of heat-steam-induced skin damage.